Psychological and nutritional correlates of objectively assessed physical activity in patients with anorexia nervosa. (2nd July 2020) - Grosser, Julia; Hofmann, Tobias; Stengel, Andreas; Zeeck, Almut; Winter, Sibylle; Correll, Christoph U.; Haas, Verena
Abstract: Background: Physical activity (PA) plays a role in the course of anorexia nervosa (AN). Objective: To assess the association between PA, nutritional status and psychological parameters in patients with AN. Method: Using a wearable activity monitor, PA was assessed in 60 female AN inpatients, by step count and time spent in 4 metabolic equivalent (MET)‐intensity levels: sedentary behaviour, light, moderate and vigorous PA. In addition, BMI, psychological (patient‐reported outcome questionnaires) and nutritional parameters (body fat, energy and macronutrient intake) were assessed. Results: The study population spent little time in vigorous PA. BMI on admission and discharge was higher when more time was spent in sedentary behaviour, and lower with more time spent in light PA. Relationships between PA and patient‐reported outcomes were weak and limited to an association between vigorous PA and compulsiveness. Low fat mass was associated with more time spent in light PA, while subjects with higher step counts showed less intake of energy, carbohydrates and fat. Conclusion: The relationship between inadequate food intake and increased PA in patients with AN requires further investigation.